2020
DOI: 10.5194/tc-14-2629-2020
|View full text |Cite
|
Sign up to set email alerts
|

Classification of sea ice types in Sentinel-1 synthetic aperture radar images

Abstract: Abstract. A new Sentinel-1 image-based sea ice classification algorithm using a machine-learning-based model trained in a semi-automated manner is proposed to support daily ice charting. Previous studies mostly rely on manual work in selecting training and validation data. We show that the readily available ice charts from the operational ice services can reduce the amount of manual work in preparation of large amounts of training/testing data. Furthermore, they can feed highly reliable data to the trainer by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Other alternatives for assimilating extent are MASIE (Multisensor Analyzed Sea Ice Extent: Fetterer et al, 2010) and IMS (Interactive Multisensor Snow and Ice Mapping System: Helfrich et al, 2007), as done by the GOFS 3.1 system for example. Automatic ice type classification from SAR is also possible now -for example the algorithm developed by Park et al (2020) and upgraded by Boulze et al (2020) will become operationally distributed by CMEMS in 2021.…”
Section: Evaluation Of Forecasts With Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other alternatives for assimilating extent are MASIE (Multisensor Analyzed Sea Ice Extent: Fetterer et al, 2010) and IMS (Interactive Multisensor Snow and Ice Mapping System: Helfrich et al, 2007), as done by the GOFS 3.1 system for example. Automatic ice type classification from SAR is also possible now -for example the algorithm developed by Park et al (2020) and upgraded by Boulze et al (2020) will become operationally distributed by CMEMS in 2021.…”
Section: Evaluation Of Forecasts With Assimilationmentioning
confidence: 99%
“…Arctic sea ice has been in great decline in the last number of years (Meier, 2017). Perovich et al (2018) report that in 2018, the summer extent was the sixth lowest and the winter extent was the second lowest in the satellite record . Moreover, surface air temperatures in the Arctic continued to warm at twice the rate relative to the rest of the globe, and Arctic air temperatures for the past 5 years (2014)(2015)(2016)(2017)(2018) have exceeded all previous records since 1900 (Overland et al, 2018), which will also contribute to future sea ice decline if it continues.…”
Section: Introductionmentioning
confidence: 99%
“…The pertinence of different attributes for sea-ice characterization has been investigated for both SAR [4], [7]- [14] and optical imagery [15], [16]. In some studies, e.g., the entropy was found to be well suited for separating sea ice types [13]. In other studies, however, the same parameter was found to be less relevant for sea ice classification [8], [11], and less useful for detection of leads in the ice [9], [12].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have been devoted to classifying sea ice and open water on SAR images, including threshold-based methods [4], expert systems [5], and machine learning (ML) methods. Since the 21st century, ML has become the mainstream method, such as the neural network (NN) model [6], [7], support vector machine (SVM) [8], [9], and random forest (RF) classifier [10].…”
mentioning
confidence: 99%
“…A typical procedure of these CNN-based models includes This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ two steps: 1) inputting an SAR image chip (e.g., with the size of 13 × 13, 45 × 45, or 50 × 50 [10], [17]- [20]) into several stacking pairs of CNN + max-pooling layers to extract downscaled feature using FC NN layers to connect the downscaled feature maps and output the class of the central pixel of the input chip. The drawback is that we need manually construct training/testing samples for each pixel of an image, increasing the workload and the storage burden of memory.…”
mentioning
confidence: 99%